Brazilian textile and fashion industry: social aspects towards circular economy - Galatti, Leticia Gabriela (2022)
It is estimated that the Brazilian textile and fashion industry has a social and economic impact on eight million people. But while access to the fashion industry is facilitated for a large mass of low-skilled workers, the social promotion through work and income is difficulted due to the low labour valuation policies and short-term relationships in the industry. As the circular economy is a concept that claims to support sustainable development and mitigate the social problems caused by rapid global economic growth, through the transition to circularity the Brazilian textile and fashion industry could design and operate a new system that can narrow the gaps caused by the current power dynamics and linear system. Since the fashion ecosystem is very fragmented, global standardized circular solutions are unlikely to emerge soon. Therefore, the Brazilian textile and fashion industry needs to find its approach to meet the circularity. As the social and labour aspects in a circular textile and fashion industry are still little known, the main objective of this study was to promote the discussion of this topic considering the Brazilian context. The research was conducted in two phases, the first was a comprehensive literature review that discussed the manufacturing base as a strategic issue for the circular transition; and the second included the identification in the literature (and validation with experts) of indicators capable of measuring the social innovation capacity of the work in a circular economy. These results have the potential to contribute to future research and development of methods to measure and monitor the social aspects of work in a circular textile and fashion industry